Musculoskeletal loading during the round-off in female gymnastics: the effect of hand position - Farana, R.; Jandacka, D.; Uchytil, J.; Zahradnik, D.; Irwin, G. (Sports Biomechanics, 2014)
Chronic elbow injuries from tumbling in female gymnastics present a serious problem for performers. This research examined how the biomechanical characteristics of impact loading and elbow kinematics and kinetics change as a function of technique selection. Seven international-level female gymnasts performed 10 trials of the round-off from a hurdle step to flic-flac with `parallel` and `T-shape` hand positions. Synchronized kinematic (3D-automated motion analysis system; 247 Hz) and kinetic (two force plates; 1,235 Hz) data were collected for each trial. Wilcoxon non-parametric test and effect-size statistics determined differences between the hand positions examined in this study. Significant differences (p < 0.05) and large effect sizes (ES>0.8) were observed for peak vertical ground reaction force (GRF), anterior-posterior GRF, resultant GRF, loading rates of these forces and elbow joint angles, and internal moments of force in sagittal, transverse, and frontal planes. In conclusion, the T-shape hand position reduces vertical, anterior-posterior, and resultant contact forces and has a decreased loading rate indicating a safer technique for the round-off. Significant differences observed in joint elbow moments highlighted that the T-shape position may prevent overloading of the joint complex and consequently reduce the potential for elbow injury.